Determination of the cosmic-ray-induced neutron flux and ambient dose equivalent at flight altitude. (July 2015) - Pazianotto, M T; Cortés-Giraldo, M A; Federico, C A; Gonçalez, O L; Quesada, J M; Carlson, B V
Abstract: There is interest in modeling the atmosphere in the South Atlantic Magnetic Anomaly in order to obtain information about the cosmic-ray induced neutron spectrum and angular distribution as functions of altitude. In this work we use the Monte Carlo codes MCNPX and Geant4 to determine the cosmic-ray-induced neutron flux in the atmosphere produced by the cosmic ray protons incident on the top of the atmosphere and to estimate the ambient dose equivalent rate as function of altitude. The results present a reasonable conformity to other codes (QARM and EXPACS) based on other parameterizations.